Sudden onset anhidrosis in an otherwise healthy male - Clara Michelle Tan Hwei Sian Tan; Rayson Lee; Janet Pei Ling Dua (Wiley, 2023)
Abstract Acquired idiopathic generalised anhidrosis (AIGA) is a rare disorder that is characterised by sudden onset generalised absence of sweating without any dermatological, neurological or sweat gland abnormalities. AIGA predominately affects young males, mostly involving patients of Asian descent. There have been approximately 100 reported cases worldwide, most of which were reported in Japan. In Singapore, it is rarely seen with one case series on 15 cases of AIGA reported in a 2014 study. Here, we present a case of AIGA who responded well to conservative management with sweating activity.